Effect of overtime towards construction labour: a contractor’s perspective / Muhammad Nashrul Hazim Shaharudin and Wan Faida Wan Mohd Azmi - Shaharudin, Muhammad Nashrul Hazim; Wan Mohd Azmi, Wan Faida (2023)
Overtime is common in the construction industry where projects often require a shorter completion time. Contractors use overtime as a way to speed up construction work but it comes with drawbacks. Overtime workers are less productive, leading to increased project costs. This study aimed to identify the effects of overtime on construction labor, investigate its causes, and propose solutions. Questionnaires were distributed to Grade 7 contractors in Johor Bahru, and the data was analyzed using statistical methods. Akta Kerja 1955 is a deed that sets the minimum employment standards for private sector workers, regardless of union membership. It provides a comprehensive framework for employment laws, covering various aspects such as wages, rest days, working hours, annual leave, sick leave, maternity protection, termination of contracts, and the hiring of foreign workers. The study found that overtime reduces labor productivity, causes fatigue, increases absenteeism, lowers worker morale, and raises accident rates on construction sites. Overall, the study successfully achieved its objectives and used data collection and analysis to support its findings.